Regulation of troponin T expression during muscle development in sea bream Sparus auratus Linnaeus: the potential role of thyroid hormones - Campinho, Marco António (2006)
In the sea bream Sparus auratus three stage-specific fast troponin T (fTnT) isoforms have been cloned and correspond to embryonic-, larval- and adult-specific isoforms. Characterisation, using database searches, of the putative genomic organisation of Fugu rubripes and Tetraodon nigroviridis fTnT indicates that alternative exon splicing in the 59 region of the gene generates the different isoforms. Moreover, comparison of teleost fTnTs suggests that alternative splicing of fTnT appears to be common in teleosts. A different temporal expression pattern for each fTnT splice variant is found during sea bream development and probably relates to differing functional demands, as a highly acidic embryonic form (pI 5.16) is substituted by a basic larval form (pI 9.57). Thyroid hormones (THs), which play an important regulatory role in muscle development in flatfish and tetrapods, appear also to influence TnT gene expression in the sea bream. However, THs have a divergent action on different sea bream TnT genes and although the slow isoform (sTnT1) is TH-responsive, fTnT, sTnT2 and the itronless isoform (iTnT) are unaffected. The present results taken together with those published for flatfish seem to suggest differences may exist in the regulation of larval muscle development in teleosts.